Respuesta :

Answer:

Step-by-step explanation:

Ver imagen 25casadosisabella

Answer:

n = -9

Step-by-step explanation:

Given the equation, -3(n + 5) = 12, the goal is to solve for the value of n.

Use the distributive property of multiplication, where it states that:

a(b + c) = ab + ac

Distribute -3 inside the parenthesis:

-3(n + 5) = 12

-3n - 15 = 12

Next, add 15 to both sides:

-3n - 15 + 15 = 12 + 15

-3n = 27

Divide both sides by -3 to solve for n:

[tex]\frac{-3n}{-3} = \frac{27}{-3}[/tex]

n = -9

Therefore, the value of n = -9.